An integration of uml use case diagram and activity diagram with Z language for formalization of library management system - Zainab Hassan Muhamad; Dhafer AbdulAmeer Abdulmonim; Bashar Alathari (International Journal of Electrical and Computer Engineering (IJECE), 2019)
Unified Modeling Language (UML) is the effective standard for modeling object-oriented software systems. However, the ambiguity of semantics and the absence of consistency among UML diagrams lead to lack of precisely defining the requirements of a system. On the other hand, formal methods are techniques and tools use the mathematical notations, and they involve the precise syntax and semantics of the unambiguous software requirements specification. It applied in early stages of Software Development Life Cycle (SDLC). Therefore, an integrated between UML specification and formal specification is required to reduce the requirements' ambiguity and error, and to improve the quality and security of software systems. This paper proposes an approach involves the combining UML use-case diagram and activity diagrams with Z language for formalization of Library Management System (LMS). The focus of this paper is on consistency between the UML diagrams to Z Schema, and then verified by using the Z / EVEs tool.